2019
DOI: 10.1111/dme.13903
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between point‐of‐care testing and venous glucose determination for the diagnosis of diabetes mellitus 6–12 weeks after gestational diabetes

Abstract: Aim To evaluate point-of-care-testing (POCT) for the diagnosis of Type 2 diabetes mellitus 6-12 weeks post-partum in women with gestational diabetes (GDM).Methods Post-partum glucose assessment (75-mg oral glucose tolerance test, OGTT) was performed prospectively in 122 women with GDM (1 November 2015 to 1 November 2017) at Tygerberg Hospital, Cape Town, South Africa. Individuals with known pre-existing diabetes were excluded. The accuracy and clinical utility of POCT (capillary fingerprick) were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…These results are supported by a study of Coetzee where 122 women underwent OGTT eight weeks postpartum; they found a sensitivity of 89.3%, a specificity of 97%, and a PPV of 89% in fasting samples when comparing capillary and venous sampling. Similar agreements with our study were also found for the capillary sampling at 2 h [10]. The positive and negative LHRs of 16.4 and 0.2 indicate that capillary sampling at fasting and 2 h is reliable since a positive LHR above 10 indicates a high probability for correct diagnosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are supported by a study of Coetzee where 122 women underwent OGTT eight weeks postpartum; they found a sensitivity of 89.3%, a specificity of 97%, and a PPV of 89% in fasting samples when comparing capillary and venous sampling. Similar agreements with our study were also found for the capillary sampling at 2 h [10]. The positive and negative LHRs of 16.4 and 0.2 indicate that capillary sampling at fasting and 2 h is reliable since a positive LHR above 10 indicates a high probability for correct diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…Point-of-care testing (POCT) is an attractive option compared to sending the test to a laboratory. POCT has advantages considering cost and convenience and offers the immediate availability of results and the opportunity to measure P-glucose from both venous and capillary samples [10]. Not all POCT methods have enough analytical accuracy to be used in the diagnosis of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of POCT is common and can reduce inconvenience for patients, reduce laboratory costs, and be used in regions with difficult access to specialized medicine. 13,14,18 A recent study even evaluates the usefulness of POCT in diagnosing diabetes mellitus 6-12 weeks after gestational diabetes, 24 concluding that POCT is clinically useful in identifying women with diabetes at early postpartum evaluation. They also conclude that use of POCT can decrease the need for routine laboratory glucose testing after GDM and may reduce cost and increase the probability of postpartum glucose evaluation after GDM.…”
Section: Discussionmentioning
confidence: 99%
“…The device is whole blood calibrated; blood glucose values displayed therefore correspond to plasma. The analytical performance has previously been evaluated against rigorous laboratory criteria and did not exceed total allowable error in the fasting or postprandial state ( 14 ). The glucose results are reported in mmol/L.…”
Section: Methodsmentioning
confidence: 99%